Magnetic and Dielectric Properties of La and Ni Co-substituted BiFeO3 Nanoceramics - Srivastava, Amit; Singh, Ashwani Kumar; Srivastava, O. N.; Tewari, H. S.; Masood, Khalid B.; Singh, Jai (Frontiers in Physics, 2020)
The increasing plead for the realization of ultra-fast, miniaturize, compact and ultra-low power consumption in electronic as well as spintronic devices has propelled the quest for novel multiferroic materials which enable voltage control of magnetism in an energy efficient way. The present work reports the phase stability, magnetic and dielectric properties of polycrystalline Bi1-xLaxFe1-yNiyO3 (0≤x≥0.2 and 0≤y≥0.2) multiferroic ceramics synthesized through a simplistic sol-gel approach. The maneuver substitutions of La at Bi site in the BiFeO3 multiferroic eliminate the usual impurity phases. Rietveld refined XRD patterns reveals the structural evolution of orthorhombic (Pbnm) phase with the increasing Bi content at La site and further Ni substitutions at Fe sites induces the lattice distortion. A substantial enhancement in multi-ferroic behaviour has been observed for Ni and La co-substituted samples, due to the size confinement effect of nano-crystallites, the exchange interaction between Fe3+ and Ni2+ ions and corresponding change in Fe-O-Fe bond angles led by the co-substitution. The dielectric constant has observed to be increased by two-fold in the low frequency region with the La and Ni co-substitutions at A (Bi) and B (Fe) -sites respectively. The zero-field-cooled (ZFC) and field-cooled (FC) magnetization curves show spin glass like behavior with an embedded ferromagnetic component. The results indicate that the co-substitutions of La and Ni at the respective sites of Bi1-xLaxFe1-yNiyO3 (0≤x≥0.2 and 0≤y≥0.2), can significantly improve the ferromagnetic and dielectric properties of BiFeO3 nanoceramics.